Kajian Semiotik Roland Barthes pada Puisi Sawer Pengantin Sunda sebagai Usulan Bahan Ajar Puisi Rakyat di Kelas VII SMP - Wachyudin Wachyudin; Dwi Purwati; Anwar Faris; Yasifa Erida Dzulhijah; Diva Raehandika; Miftahul Malik (Badan Pengembangan dan Pembinaan Bahasa, 2024)
The research was carried out to find out the meaning contained in the bride's sawer poem which will later be used as a proposal for teaching materials for class VII junior high school folk poetry. The bride's sawer poems studied are sawer poems with the rules of pupuh kinanti and asmarandana, which will be analyzed using the Roland Barthes semiotics approach. Denotative meaning and connotative meaning are important points in this study because the results of the meaning analysis will be used as a proposal for teaching materials for folk poetry in grade VII of junior high school, which is then made a folk poetry learning module. The research method used is a qualitative descriptive method that aims to understand the written and oral language of the community and observable behavior. The results of the analysis show that the connotative meaning of the Sundanese bride sawer poem is a request to God so that the expectations of the bride and groom are always fulfilled and get the best in their married life. The text of the Sundanese bride sawer poem has five meanings denotatively: piety to God, hope, responsibility, affection, and ethics. The denotative and connotative meanings that have been analyzed can be used as a reference for the proposed teaching materials for folk poetry in grade VII of junior high school. Because in phase D of the independent curriculum, students are expected to be able to read and watch the content of folk poetry. AbstrakPenelitian dilakukan guna mengetahui makna yang terdapat pada puisi sawer pengantin yang nantinya akan dijadikan sebagai usulan bahan ajar puisi rakyat kelas VII SMP. Puisi sawer pengantin yang dikaji adalah puisi sawer dengan aturan pupuh kinanti dan asmarandana, yang akan dianalisis menggunakan pendekatan semiotika Roland Barthes. Makna denotatif dan makna konotatif menjadi poin penting dalam penelitian ini karena hasil analisis makna tersebut akan bisa digunakan sebagai usulan bahan ajar puisi rakyat di kelas VII SMP, yang selanjutnya dibuatkan modul pembelajaran puisi rakyat. Metode penelitian yang digunakan adalah metode deskriptif kualitatif yang bertujuan untuk memahami bahasa tulis dan lisan masyarakat serta perilaku yang dapat diamati. Hasil analisis menunjukkan bahwa makna konotatif dari puisi sawer pengantin Sunda adalah permohonan kepada Tuhan agar harapan kedua mempelai senantiasa terpenuhi dan mendapatkan yang terbaik dalam hidup rumah tangga mereka. Teks puisi sawer pengantin Sunda memiliki lima makna secara denotatif: ketakwaan kepada Tuhan, harapan, tanggung jawab, kasih sayang, dan budi pekerti. Makna denotatif dan konotatif yang telah dianalisis bisa dijadikan sebagai acuan dari usulan bahan ajar puisi rakyat di kelas VII sekolah menengah pertama. Karena pada fase D kurikulum merdeka peserta didik diharapkan mampu untuk membaca dan memirsa isi dari puisi rakyat.